2018
DOI: 10.1055/s-0038-1632400
|View full text |Cite
|
Sign up to set email alerts
|

Patients Screening Positive for Body Dysmorphic Disorder Show No Significant Health-Related Quality of Life Gain after Functional Septorhinoplasty at a Tertiary Referral Center

Abstract: Body dysmorphic disorder (BDD) is a psychiatric disorder defined by an excessive concern about one's physical appearance, especially regarding slight or imagined abnormities of the body. This study was conducted to compare postoperative quality of life (QOL) changes after primary septorhinoplasty among patients screening positive and those screening negative for BDD. Two common instruments for the screening of BDD were used namely the Dysmorphic Concern Questionnaire (DCQ) and the BDD Concern Questionnaire (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…Poor outcomes without improvement in quality of life have been observed in patients with BDD undergoing functional intervention. 14 Though BDD specifically has not been investigated in oncologic patients, it has been shown that a majority of these patients have concern, preoccupation, or avoidance of reconstructive surgery related to body image, representing an opportunity for further study. 29 Screening instruments such as the BDDQ, which was utilized in our study, are not definitive diagnostic tools for BDD, but rather suggest that BDD may be present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor outcomes without improvement in quality of life have been observed in patients with BDD undergoing functional intervention. 14 Though BDD specifically has not been investigated in oncologic patients, it has been shown that a majority of these patients have concern, preoccupation, or avoidance of reconstructive surgery related to body image, representing an opportunity for further study. 29 Screening instruments such as the BDDQ, which was utilized in our study, are not definitive diagnostic tools for BDD, but rather suggest that BDD may be present.…”
Section: Discussionmentioning
confidence: 99%
“…13 Furthermore, BDD appears to influence clinical outcomes in this population, as Bulut et al described that patients screening positive for BDD have a significantly lessened improvement in quality of life following functional septorhinoplasty. 14 In a prospective study, the BDDQ has been used to identify patients who may be unsuitable for surgical intervention, suggesting a role for preoperative evaluation of BDD. 15 It should be noted that the BDDQ does not reflect an actual diagnosis of BDD but may indicate patients that warrant further psychiatric evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…8 In an earlier study by Bulut et al, the comparison of BDD-positive screened patients was also found to be lower than the negative screened patients but in a smaller cohort. 17 Patients with BDD have reportedly a high rate of psychiatric comorbidities, especially depression and anxiety, and seek aesthetic surgery more frequently. 23,24 In patients seeking aesthetic treatment including rhinoplasty, a higher rate of psychiatric diseases has also been reported by multiple authors.…”
Section: Current Literaturementioning
confidence: 99%
“…[8][9][10] Despite the high prevalence of BDD and its association with higher levels of depression and anxiety, the prevalence of these psychiatric conditions in rhinoplasty patients is understudied 11,12 and their effect on rhinoplasty outcomes and QoL remains unclear. 6,[13][14][15][16][17] It was hypothesized that patients screening positive for BDD, anxiety, and depression do not show elevated postoperative QoL after SRPL. Investigation design was the prospective assessment of the most common psychiatric disorders (BDD, depression, anxiety disorder) in a large cohort of rhinoplasty patients and their effect on pre-and postoperative QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Body dysmorphic disorder (BDD) in individuals seeking SRPL is recognized as a contraindication for surgery due to these considerations. [7][8][9] Characterized by excessive concern about one's physical appearance and daily distress related to perceived slight or imagined defects, the nose often becomes a focal point of concern in BDD. 10 for this purpose.…”
mentioning
confidence: 99%